A new variety of Solanum sisymbriifolium obtained by in vitro polyploidization - Iannicelli, Jessica (Instituto de Pesquisas Jardim Botânico do Rio de Janeiro, 2024)
Solanum sisymbriifolium is a shrub native to South America and considered a weed of several important crops. Despite this, this species has proven nematicidal capacity and medicinal properties, due to its ability to produce alkaloids. Thus, the objective of this work was to adjust a reliable protocol to obtain in vitro polyploid plants of S. sisymbriifolium to generate germplasm that serves as the basis for a breeding program of this species aimed to improve the sanitary conditions of horticultural crops with less impact on the environment.
Keywords: Ciencias Exactas y Naturales; Ciencias Biológicas